2016
DOI: 10.11648/j.sjph.20160406.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaemia Among Young Adult Females in Two Selected Grama Niladhari Areas in the Southern Province of Sri Lanka

Abstract: Anaemia is a global health problem and its impact is felt in Sri Lanka as well. Anaemia is characterized by less than the normal quantity of hemoglobin in the blood. Anaemia occurs at all stages of life, but is particularly prevalent in women of reproductive age, pregnant women and children. This study was conducted to investigate the prevalence of anaemia in two rapidly developing administrative units in Southern Province of Sri Lanka. A cross-sectional study was conducted in Hungama and Hiththatiya middle ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our study revealed no significant association between BMI and anaemia. A similar study was conducted in Srilanka, in which BMI had no significantly associated with presence of anaemia [31]. In another similar kind of study, it was found that odds of anaemia decreased with obesity [32].…”
Section: Discussionmentioning
confidence: 84%
“…Our study revealed no significant association between BMI and anaemia. A similar study was conducted in Srilanka, in which BMI had no significantly associated with presence of anaemia [31]. In another similar kind of study, it was found that odds of anaemia decreased with obesity [32].…”
Section: Discussionmentioning
confidence: 84%